A Systematic Review of Modified Schema-Based Instruction for Teaching Students with Moderate and Severe Disabilities to Solve Mathematical Word Problems. (June 2021) - Clausen, Amy M.; Tapp, Melissa C.; Pennington, Robert C.; Spooner, Fred; Teasdell, Annette
Modified schema-based instruction (MSBI) is a strategy to teach mathematical word problem solving to students with moderate and severe disabilities (MSD). In this comprehensive review, we explore the current state of research on MSBI to determine whether MSBI is an evidence-based practice (EBP) for students with MSD. We reviewed 12 studies, of which 11 met quality standards. Thirty-nine participants, all of whom participated in statewide alternate assessments, were included in these studies, the majority of whom were middle school students with intellectual disability. Four research teams explicitly targeted state content standards. The researcher served as interventionist in 82% of the studies. Although the overall effect size was very large (1.0 Tau), our findings suggest that MSBI is not yet an EBP for students with MSD. We provide an overview of current contextual factors and suggestions for future researchers to continue the investigation of MSBI.